Konsep Istiqamah Dalam Islam - Pathur Rahman (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2018)
Human life has not all come down to even more improvements that lead to destruction and destruction. This is due to a lack of determination (Istiqamah). Islamic education wants to create a place towards achieving benefits for humans themselves. Istiqamah attitude is obtained by doing something optimally, in accordance with science, not excessive, and sincerely selfless. With istiqamah it will produce a struggling yet calm and optimistic person. These three things will lead someone to the goal of Islamic education as a servant of Allah, as a caliph, and also happiness of the world and the hereafter.